Implikasi Penyimpangan Gangguan Fethisme dalam Kesehatan Mental - Ulin Nihayah; Riza Umami; Luthfi Kharisma N. A; Nabila Anis Saputri (Indonesian Journal of Counseling and Development, 2021)
A fetish case is a case in which the perpetrator has sexual aberrations with body parts or an object (called a fetish) in order to get sexual stimulation and satisfaction. The perpetrator will be stimulated on a body part or an object which for some people is just a stimulus. The object will make the basis of fantasy and help romance but is not a substitute for more conventional sexual activities, fetishes that may be on body parts such as the buttocks of the eyes while on inanimate objects such as cloth, underwear, shoes, etc. this fetish is a form of sexual crossing which, if carried out continuously, can result in on going stress and disrupt the mental health of the perpetrator. The research method used in writing this journal is descriptive qualitative which is used to examine natural objects, by untilizing qualitative data and then sharing descriptively. The results of the analysis show that fetish behavior can affect mental health and can be cured by treatment in the form of sex education and Islamic therapy. Sex education is given, among others, about the ethics of asking permission to look at things, avoiding and various forms of sexual stimulation, provide lessons on how to protect yourself from despicable acts if you are not married, provide understanding and counseling related to the dangers of adultery. Meanwhile, Islamic therapy includes submission in prayer, but suggestions for self-introduction and self- authoritarian acts.